Global Demographic Change - On Longevity - Groth, Hans (Mednarodno inovativno poslovanje, 2019)
In this paper the author examines patterns and prospects for the leading causes of death in countries across the globe. An explicit focus is on the diversity and ongoing dynamics of mortality. New factors promising to contribute to a longer and healthier life help to draw a picture of our life in the decades to come and its opportunities for business and society. Based on this the author presents several scenarios for forecasting of life expectancy with different degrees of probability.
Keywords: demografske spremembe; dolgoživost; forecasting life expectancy; longevity; nominal demographic change; pričakovana življenjska doba